Improving national hospice/palliative care service symptom outcomes systematically through point-of-care data collection, structured feedback and benchmarking - Currow, David C.; Allingham, Samuel; Yates, Patsy; Johnson, Claire; Clark, Katherine; Eagar, Kathy (Supportive care in cancer, 2015)
Purpose Every health care sector including hospice/palliative care needs to systematically improve services using patient-defined outcomes. Data from the national Australian Palliative Care Outcomes Collaboration aims to define whether hospice/palliative care patients’ outcomes and the consistency of these outcomes have improved in the last 3 years. Methods Data were analysed by clinical phase (stable, unstable, deteriorating, terminal). Patient-level data included the Symptom Assessment Scale and the Palliative Care Problem Severity Score. Nationally collected point-of-care data were anchored for the period July–December 2008 and subsequently compared to this baseline in six 6-month reporting cycles for all services that submitted data in every time period ( n = 30) using individual longitudinal multi-level random coefficient models. Results Data were analysed for 19,747 patients (46 % female; 85 % cancer; 27,928 episodes of care; 65,463 phases). There were significant improvements across all domains (symptom control, family care, psychological and spiritual care) except pain. Simultaneously, the interquartile ranges decreased, jointly indicating that better and more consistent patient outcomes were being achieved. Conclusion These are the first national hospice/palliative care symptom control performance data to demonstrate improvements in clinical outcomes at a service level as a result of routine data collection and systematic feedback.